A THEROPOD DINOSAUR FROM THE LATE JURASSIC CAÑADÓN CALCÁREO FORMATION OF CENTRAL PATAGONIA, AND THE EVOLUTION OF THE THEROPOD TARSUS (Ameghiniana, 2017)
A fragmentary postcranial skeleton from the Late Jurassic (Oxfordian–Tithonian) Cañadón Calcáreo Formation of Chubut, Argentina,represents a new taxon of theropod dinosaur, which is here described as Pandoravenator fernandezorum gen. et sp. nov. This material representsthe first Late Jurassic theropod known from Argentina. Pandoravenator fernandezorum is characterized by strongly elongated postzygapophysesin the caudal vertebrae and an unusual tarsal joint, with the astragalus showing two distal tubercles and a very low and laterallyinclined ascending process. Phylogenetic analyses indicate that the new taxon is a basal tetanuran, although its exact phylogenetic positionwithin basal tetanurans remains uncertain, due to the fragmentary nature of the remains and the lack of consensus among the differentphylogenetic analyses. The tarsus of P. fernandezorum shows an intermediate morphology between that of basal theropods and more derivedtetanurans. It is especially noteworthy for the presence of a suture between the distal astragalar condyles and the anteroproximal extension ofthe astragalus, including the ascending process. This indicates that a separate ossification of the ascending process of the astragalus waspresent in this taxon, and, in a phylogenetic context, thus provides evidence that the origin of the ascending process and the astragalar bodyfrom separate ossifications was already present at the base of Averostra.